Aspek Digital Marketing Bagi Kemajuan Disc Jockey - Liliana Dewi; Marco Tantomo (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
This study aimed to find out the Evaluation of Marketing Strategies for Shift Paradigm. The method used in this research was a qualitative method. Research subjects involved 7 consumers, Shift Paradigm members, expert marketing, and lecturers EP6. This study found Paradigma Shift’s marketing strategy was not effective. Using digital marketing was recommended to maximize marketing strategies for Shift Paradigm. In addition to a digital marketing, involving event planner and promoter were also recommended to reach the marketing targets of the shift paradigm. The results of this study are expected to serve as review materials for the Evaluation of Marketing Strategies for Shift Paradigm and other Disc Jockey Management.